Aspectos do pensamento matemático na resolução de problemas: uma apresentação contextualizada da obra de Krutetskii - Wielewski, Gladys Denise (2005)
This doctorate thesis aims to identify the characteristics and the dimensions of mathematical thinking in experimental and theoretical terms which may be useful to teachers with respect to teaching processes, development of mathematical ideas and the delineation of learning contexts. Our study began with a detailed analysis of the work of Krutetskii (1968). This book is very rich in theoretical examples and reflections. It is, however, a completely psychological work and provided few indications of the more general mathematic knowledge and thinking. For this reason we added detailed information about the work of other authors such as Gowers, Poincaré, Boutroux, Otte and Kurz, and this added other dimensions which assisted our understanding of the nature of mathematics. These authors were concerned with the problems of cognitive styles, cultural and historical differences, differences that are the results of mathematics itself and distinctive ways of representing mathematics. The experimental dimensions consisted of analysis of data obtained from qualitative research with students whereby one was taken from the literature (Krutetskii) and the other an exploratory survey which we carried out for the purposes of this thesis. Krutetskii carried out an experimental investigation involving 201 Russian students with different mathematic abilities, attending elementary school. These students were presented with a number of different series of mathematic problems and their mathematic abilities were observed during the problem solving process. In our survey we carried out case studies exploring mathematic problem solving involving 13 students from the Federal University of Mato Grosso with 9 students from the Mathematics/Education course and 4 students from the Computer Sciences Course. The exploratory survey was organized into 3 phases. The first was the completion of a questionnaire with subjective questions about Mathematics and preferred ways of thinking and dealing with this subject. The second phase was reserved for the solution of 13 varied mathematical problems. The final phase was the completion of another questionnaire with subjective questions which sought to obtain information about the experiences of the students when solving the problems set. With our exploratory survey we were able to document and verify several parameters and characteristics of mathematical thinking which were described in the theoretical chapters as well as being able identify the problems themselves and the experience of solving them also influenced mathematical thinking. As a general result we concluded that mathematical thinking must be considered in the light of different parameters since this can help to characterize more complete mathematical thinking